جمعيات التمويل الفردي التعاوني كبديل تمويلي للأفراد والأسر "دليل من المملكة العربية السعودية" - Al Ajlouni, Ahmed; Almosabbeh, Imadeddin (مجلة العلوم الإدارية و الإقتصادية, 2019)
This study aims at developing a measuring tool for the performance of Societies of personal financing; it also aims at identifying the extent of their spread in the Saudi community and the motivation behind participation in them both in the saving and the financing side. The study applied this measurement tool at a sample of Saudi citizens and residents who deal with this financing mode. Researchers use statistical descriptive method to analyze the respondents of 519 sample members. Among the most important results of the analysis is the wide spread of funding Societies for their financing and savings solutions in Saudi Arabia. Results also showed that saving is the key factor behind participation in Societies; and that religious background of the sample supported the tendency toward sharing Societies. It showed that the lack of adherence by some participants to pay their financial obligations considered the main drawback of Societies. The study recommends that official agencies support this model of informal personal finance and provide supporting legal and institutional environment to boost that.